التنظيم القانوني لتسوية المنازعات الناجمة عن تداول الأوراق المالية في أسواق الأوراق المالية - دراسة تحليلية - عبدالقادر, دانا حمه باقي (Journal of Legal and Political Studies, 2013)
The Stock Exchange (Markets) is one of the main tools of economic growth to any country in way of development. That is because to its role in mobilizing and allocating savings in investment channels that is beneficial to the local economy as well as to the capital owners. Therefore, the investment in those markets is one of the important options which require establishing elements and foundations that ensure its success and stability. Including, there must be some legal rules that effectively settle between stock’s disputes and cases. On this way, this paper explores the nature of those disputes and how the Iraqi law settles it, at the same time it explores legal nature of cases. Thereby, this paper will reach some conclusions and results which show the failure of Iraqi regulation to how settle between those cases, and selecting lack of provisions in that regulation. Furthermore, it also raises a number of recommendations, most importantly making recourse to arbitration as one of the optional choice in order to settle cases, and it should be clear rules and explicit provisions adopting regarding to the procedures, conditions and how to enforce the arbitral decisions..
Keywords: Stock Exchange; Economic growth; Arbitration; Regulation